Navigating physical activity after a nerve injury in the arm and hand - Linda Evertsson; Cecilia Mellstrand Navarro; Christina Turesson (PLoS ONE, 2026)
Peripheral nerve injuries in the arm and hand can lead to significant challenges, impacting every aspect of a person’s life. Still, rehabilitation largely focuses on hand exercises, emphasizing motor function recovery. Targeting sensory relearning poses a significant challenge for the brain, demanding neural adaptation and reorganization. While, physical activity is not a standard component of current rehabilitation, yet it supports recovery and promotes nervous system health across other various conditions. However, it remains unclear whether nerve injuries affecting the arm, hand, or fingers contribute to decreased levels of physical activity. Qualitative methods, specifically semi-structured interviews with content analysis, were used to gain a deeper understanding of participants´ experience of change in physical activity after a nerve injury to the arm and hand. Data from in total 20 participants with different levels of nerve injury in the arm and hand were analysed with content analysis. Two themes emerged ‘barriers’ and ‘facilitators’ for being physically active after the nerve injury. The themes displayed three dimensions: internal factors (e.g., prior experience of physical activity and personality traits), physical factors (e.g., pain and hand function) and external factors (e.g., support from family and health care professionals). Key findings indicate that a nerve injury to the arm and hand leads to decrease in physical activity, regardless of injury severity. Previously inactive individuals faced barriers too significant to overcome independently, highlighting the need for targeted support to facilitate physical activity following nerve injuries. These findings may offer new insights into potential rehabilitation strategies.